2019
DOI: 10.1016/j.socscimed.2019.05.051
|View full text |Cite
|
Sign up to set email alerts
|

The impact of diabetes on labour market outcomes in Mexico: A panel data and biomarker analysis

Abstract: Background to series CHE Discussion Papers (DPs) began publication in 1983 as a means of making current research material more widely available to health economists and other potential users. So as to speed up the dissemination process, papers were originally published by CHE and distributed by post to a worldwide readership. The CHE Research Paper series takes over that function and provides access to current research output via web-based publication, although hard copy will continue to be available (but subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 66 publications
2
7
2
Order By: Relevance
“…Our findings somehow support those obtained by another study concluding that only in case time since diagnosis of diabetes was greater than 20 years, so older people, wages were reduced (Seuring et al, 2016). The significant role of diabetes as a determinant of (lower) household income only in advanced age could be the result of the diabetes type that these people are more likely to suffer from, diabetes type II.…”
Section: 2 Diabetes and Incomesupporting
confidence: 91%
See 3 more Smart Citations
“…Our findings somehow support those obtained by another study concluding that only in case time since diagnosis of diabetes was greater than 20 years, so older people, wages were reduced (Seuring et al, 2016). The significant role of diabetes as a determinant of (lower) household income only in advanced age could be the result of the diabetes type that these people are more likely to suffer from, diabetes type II.…”
Section: 2 Diabetes and Incomesupporting
confidence: 91%
“…Our results confirm the burden of diabetes on income and earnings, which has already widely studied in the literature. Most of the studies conclude that those who have diabetes suffer from decrements in their earnings (Mayfield et al, 1999;Valdmanis et al, 2001;Plaveev et al, 2006;Schofield et al, 2014;Schofield et al, 2015), although some have reported that diabetes has no significant effect on wages (Seuring et al, 2016), which would be contradicted by our findings. Tables S4 and S5 included in the Appendix show the average marginal effects from the ordered probit regression (Model D) on monthly household income for females and males, respectively.…”
Section: 2 Diabetes and Incomecontrasting
confidence: 71%
See 2 more Smart Citations
“…Effects on labourmarket dropout and presenteeism are based on studies from the USA 207,208 and Mexico. 209,210 Although the diversity of sources is larger for absenteeism-with studies from the USA, 211 Mexico, 210 India, 212 Iran, 213 and Namibia 214 -it is unclear to what extent these labour-market effects accurately capture the situation in sub-Saharan Africa. For instance, the combination of limited capabilities for management of blood sugar levels and a shortage of preventive treatment is likely to lead to high rates of severe complications in the long term, hence potentially increasing the rate of labour-force dropout.…”
Section: The Lancet Diabetes and Endocrinology Commissionmentioning
confidence: 99%